Analisis Sistem Monitoring Daya dan Kendali Saklar Berbasis ESP8266 - Ari Yuliati (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2021)
The system of remote monitoring electrical and control is a device that was created based on the problem of monitoring the need for electrical power connected to electrical devices and as a development of previous research. This monitoring and control system aims to determine the use of electric power at any time by reading the electric voltage and current with a voltage sensor and a current sensor respectively. The electrical power value that has been detected is forward to firebase and thingspeak, then transmit to the android application. This system is applied for usage monitoring of rooms connected to electrical devices as an indicator of room usage. The results of this system test are the minimum power load that can be detected is 80Watt, some loads still have a high error, but the system is able to detect at a certain distance effectively.